Crime in a Psychological Context : From Career Criminals to Criminal Careers. - Walters, Glenn D. (SAGE Publications, 2011)
This engaging book presents a contextual psychological interpretation of crime. It covers essential topics including psychopathy, antisocial personality disorder, and criminal lifestyle. The author's compelling analysis explains criminal behavior, by showing how the criminal lifestyle is capable of integrating two seemingly incompatible crime paradigms: the career criminal paradigm and the criminal career paradigm. Starting with a context for criminality, and then moving from particular conceptions of crime to more evidence-based theories, this volume challenges students to think in a differen.